Timor-Leste : The Business Regulatory Environment - World Bank (Washington, DC, 2014)
Timor-Leste started as an independent country facing some very difficult challenges. The country was extremely short of skilled human resources and remains so. It faced the challenge of moving from the inherited Indonesian legal system to a new legal system based on the lusophone tradition. Added to this was the adoption of Portuguese as a new official language. Good work has been done by the Government and the Parliament in addressing the constraints and creating the building blocks of the legal and regulatory framework needed for competitive and equitable private sector development. In setting its development agenda for the business regulatory environment we recommend that the Government take account of the realities in Timor-Leste by adopting several key guiding principles: accept that everything cannot be done at once. ; accept the reality that institutions cannot be built overnight; adopt pragmatic solutions which take this fact into account and minimize the administrative burden; in building institutions, focus on those that are identified as bottlenecks and impediments to private sector investment and growth; enlist the support and resources available in the private sector, not only in diagnosing problems but also in devising and implementing pragmatic solutions; and make maximum use of the support available from the donors and other external sources to support this agenda.